The profile of students' metacognition and students' critical thinking: Is it correlate? - Mahfira, Cladinea; Novia, Hera; Rusyati, Lilit (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
According to ATCS21, critical thinking is crucial for navigating modern complexities, driving innovation, and contributing to society. Research has shown a simultaneous occurrence of metacognitive strategies and high-level cognitive functions like critical thinking, as metacognition helps individuals monitor and adjust their cognitive processes (Mitsea & Drigas, 2019; Yerdelen-Damar & EryÄ±lmaz, 2021). This study aimed to examine the profile of students' critical thinking and metacognition, and their correlation. Using a descriptive survey method, data were collected from 60 junior high school students via the Metacognitive Awareness Inventory (MAI) and Critical Thinking Test (Cronbach's Alpha 0.725). Generally, students' metacognition, in terms of knowledge and regulation, meet an OK criteria, indicating awareness and effective use of learning strategies. While students displayed good abilities in determining assumptions and drawing conclusions while the ability to estimate implications, create questions and determine goals, apply concepts, manage information and differentiate points of view still needs to be improved. Furthermore, there is a positive correlation between students' metacognitive and critical thinking in general. These findings are able to provide valuable insights that can be utilized to enhance the development of metacognitive and critical thinking.